FROM NATIONAL TO INTERNATIONAL: NEW ASPECTS IN THE WORK OF SUBODH GUPTA - sharma, Rohita; Randhawa, Amandeep Kaur (International Journal of Psychosocial Rehabilitation, 2020)
Art is known as expressive tool of communication, has always responded to its immediate realities. The responses are always indirect, so artists use different tools to express their emotions. And In today’s world every discipline is inter-linked with one another in some way. All facts of life and area of knowledge are influenced by science, innovation and technology. From the last quarter of 20th century, artists started to engage with non-traditional mediums to respond to our present crises because art is not bounded to paint and canvases, alternatively it has different aspects. They try to express in very unconventional way to present their works; making meaningful use of unconventional materials and having liberty of representation are the new trends in art today. With the involvement of science, technology and thoughtful material use, artists are engaging with new dialogues through their works. This paper is an effort to grasp the relation with other domains in the art practices of Indian contemporary artist Subodh Gupta. Thus, the paper is an attempt to trace the role of material and technique used in the art work of artist. Such as the utensils made of stainless steel that are much popular with the artists these days and are more in demand. In this context, some websites, other online database and observation method could be an area of study to map their role in the art work.